Biodegradation of Herbicide by the Immobilized Microbial Consortium SMC1 in Continuous Packed-Bed Biofilm Reactor - Mohanty, Satya Sundar; Jena, Hara Mohan (Frontiers in Chemical Engineering, 2022)
The present study aimed to investigate the treatment of butachlor and other commonly used herbicides by the synthetically formulated microbial consortium SMC1 immobilized on the ceramic raschig rings in a packed bed bioreactor (PBBR). The PBBR was operated in continuous mode at various flow rates over a period of 70 days to determine the effect of Hydraulic Retention Time (HRT) and initial butachlor concentration on the removal efficiency and elimination capability of the bioreactor. It was observed that the overall operation of the bioreactor changes from being controlled by the mass transfer limitations to the bio-reaction controlled thus proposing the range of 270 to 325 mg/L/d to be the optimum operating range for the efficient removal of butachlor by the PBBR. The bioreactor is able to reduce up to 90% of the initial Chemical Oxygen Demand (COD) value while treating the mixture of herbicides. The operating parameters were optimized using response surface methodology where the feed flow rate of 2.9 mL/min, initial herbicide concentration of 454.63 mg/L, and concentration of additional nitrogen source at 1.41 g/L was found to yield maximal COD reduction. To date, a continuous study in the field of butachlor biodegradation is yet to be reported. Hence, the study could be used as a model to design a better herbicide biotreatment technology.